Effect of surface charge on wettability and electrolyte behavior on graphene surfaces using molecular dynamic simulation - Mukesh Kumar; Santosh Kumar Tamang; Maryom Dabi; Anil Kumar; Ankur Jaiswal (Scientific Reports)
Abstract The interaction between electrolytes and graphene surfaces is critical in applications such as electro-wetting and energy storage. This study employs molecular dynamics simulations to investigate the influence of surface charge on electrolyte wettability and behavior. At 0.00 eV, the contact angle is 30.33°, indicating high wettability, while an increase in surface charge reduces wettability, with the contact angle rising to 36.88° at 0.06 eV and stabilizing at 62.30° at 0.15 eV. The lateral droplet spread decreases from 37.56 nm to 34.78 nm, indicating a more compact electrolyte distribution. Temperature simulations reveal a sharp rise exceeding 2000 K within picoseconds, peaking at 2800 K at 0.15 eV before stabilizing between 100 and 200 K. Potential energy increases from 0.081 $$\:×\:$$ 107 kcal/mol to 3.520 $$\:×\:$$ 107 kcal/mol, reflecting stronger electrostatic interactions. Additionally, the electric force rises with charge, consistent with Coulomb’s law, while the diffusion coefficient decreases from 8.0 Å2/ps to 6.0 Å2/ps, indicating reduced particle mobility. These findings enhance the understanding of surface charge effects on electrolyte behavior, contributing to the optimization of electro-wetting and energy storage applications.